1990
DOI: 10.1044/jshd.5503.516
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Psychophysical Dimensions of the Perceived Speech Naturalness of Nonstutterers and Posttreatment Stutterers

Abstract: The purpose of this study was twofold: to determine through psychophysical comparison of scaling data whether speech naturalness is a prothetic or a metathetic continuum, and to examine the relationship between selected acoustic characteristics of the speech of nonstutterers and treated stutterers and listeners' judgments of their speech naturalness. Comparison of magnitude estimation and interval scaling data indicated that speech naturalness behaves like a metathetic continuum, suggesting that either scaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 15 publications
2
31
0
1
Order By: Relevance
“…Although directmagnitude estimation is the preferred method for this situation, the literature is based largely on data derived from the use of equal-appearing interval scaling. The issue of scaling method has been examined in a series of papers by Schiavetti and colleagues (Metz, Schiavetti, & Sacco, 1990;Samar & Metz, 1988;Schiavetti, 1984Schiavetti, , 1992Schiavetti, Metz, & Sitler, 1981).…”
Section: The Perceptual Representation Of Speechmentioning
confidence: 99%
“…Although directmagnitude estimation is the preferred method for this situation, the literature is based largely on data derived from the use of equal-appearing interval scaling. The issue of scaling method has been examined in a series of papers by Schiavetti and colleagues (Metz, Schiavetti, & Sacco, 1990;Samar & Metz, 1988;Schiavetti, 1984Schiavetti, , 1992Schiavetti, Metz, & Sitler, 1981).…”
Section: The Perceptual Representation Of Speechmentioning
confidence: 99%
“…13 These results indicate that only ratio scales (eg, DME, visual analog) can be used to validly scale the specified dimensions of the population of speakers under study. However, other investigators have found that speech naturalness in posttreatment stutterers 14 and breathiness in normal speakers 15 behave like a metathetic continuum, indicating that EAI scales are valid methods of measuring these attributes of speech and voice.…”
Section: Introductionmentioning
confidence: 97%
“…The effectiveness of traditional behavioral therapies used to treat stuttering has been tarnished by a highly unnatural speech end-product (Metz et al, 1990;Franken et al, 1992;Kalinowski et al, 1994), difficulty in generalization outside of clinical settings and a high propensity for relapse (Craig and Calver, 1991;Boberg and Kully, 1994;Craig and Hancock, 1995;Dayalu and Kalinowski, 2002). In addition, efficiency is compromised when enormous amounts of time (Webster, 1980;Boberg and Kully, 1985) and effort are used to indirectly inhibit stuttering by learning and implementing novel speech patterns .…”
Section: Introductionmentioning
confidence: 98%